The Chaperonopathies Diseases with Defective Molecular Chaperones - Macario, Alberto J.L; Conway de Macario, Everly; Cappello, Francesco (SpringerBriefs in Biochemistry and Molecular Biology,, 2013)
Memory lapses and occasional incoherent behavior, or intestinal cramps with diarrhea, or protracted cough with low fever, or cardiovascular syndromes, or changes in the pattern of movement of the lower limps, can be signs of an incipient chaperonopathy. Yet many physicians do not know this. Most health care professionals are unfamiliar with chaperonopathies. Clinicians do not look for them because they are unaware of them. Pathologists and clinical biochemists are unprepared to test specimens to detect chaperonopathies. Despite the large amount of information available in the literature, textbooks tend to ignore chaperonopathies. Because of the lack of systematic information in textbooks and courses, chaperonopathies are invisible to practitioners and clinical researchers. This book aims to correct this situation by providing pertinent information in an orderly manner so as to prompt the reader to look for chaperonopathies in patients and seek more information about them. The book serves as an alert signal and as a primer.